Coronavirus and European stock markets : measuring the effects of public health controls, fiscal and monetary policies - Muska, Natália (2021)
Coronavirus pandemic caused one of the most severe stock market crashes, which was followed by one of the fastest recoveries in the history. This master thesis examines the relationship between Coronavirus and European stock markets. The focus of the study is on determination of relationship between most followed and possibly most precise measures of Coronavirus – new daily reported cases and deaths and stock market returns and analysis of its evolvement with time. In addition, human control measures, fiscal and monetary policies are analysed to determine whether and how they affect stock index returns in conjunction with new reported cases and deaths from the virus. The findings suggest that significant inverse relationship is present between new Coronavirus cases and stock index returns, while relationship between new Coronavirus deaths and index returns is less significant and positive. These relationships are the strongest in the first wave of the pandemic and diminish over time. Results also suggest that there is an inverse relationship between strictness of human control measures and stock index returns. In line with the well-established theories monetary policies aimed to increase money supply and interest rate cuts on average have positive effect on stock index returns. Lastly, no distinct judgement about the relationship between the scale of pandemic related fiscal policies and index returns can be made based on available data.